Analysis of Epidemic Characteristics and Related Pathogenic Factors of 2726 Cases of Pityriasis Alba - Lv Y; Gao Y; Lan N; Sun M; Zhang C; Gao J; Wang N; Yang X (Dove Medical Press, 2022)
Yongmei Lv, Yamei Gao, Na Lan, Minghui Sun, Chenchen Zhang, Jing Gao, Na Wang, Xingyu Yang Departments of Dermatology, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, 230601, People's Republic of ChinaCorrespondence: Yongmei Lv, Department of Dermatology, The Second Affiliated Hospital of Anhui Medical University, No. 678 Furong Road, Hefei Economic and Technological Development Zone, Hefei, Anhui Province, 230601, People's Republic of China, Email yongmei_lv830@163.comPurpose: To understand the distribution characteristics of onset time, onset age and gender of pityriasis alba (PA) patients in the dermatology clinic of our hospital and to further explore the pathogenesis of the disease to provide a scientific basis for the prevention and treatment of this disease.Patients and Methods: The clinical data of 2726 outpatients with PA diagnosed for the first time from January 2016 to December 2020 were collected and descriptively analyzed.Results: The number of patients with PA was less from January to March. The peak was reached in July and August. The number of cases affected by the COVID-19 epidemic in 2020 was significantly lower than that in previous years. Furthermore, the onset age of the patients ranged from 0 to 64 years old, and the median age of the total population was 7 (3, 13) years old, including 1566 males (57.45%) and 1160 females (42.55%). The ratio of male to female was 1.35:1. The number of male patients before 18 years old was higher than that of female patients, especially in the high paroxysmal age group.Conclusion: PA can be seen all the year round, and the onset peak of the disease is from July to August every year. It occurs frequently at the age of 1 to 14 before puberty. In the season of high incidence of PA, the protection from sun and moisture retention should be strengthened for infants and adolescents.Keywords: pityriasis alba, epidemic characteristics, pathogenic factors